Penyuluhan Pengelolaan Ekonomi Keluarga Pada Ibu-Ibu PKK Perumahan Villa Muka Kuning Batam - Triana Ananda Rustam; Khadijah Khadijah (Jurnal Pengabdian Masyarakat (abdira), 2022)
This study aims to provide teaching about managing the family economy which is very important in the household. Basic lesson to financial management needs to be socialized and applied to the families of PKK mothers in the Villa Muka Kuning Batam Housing because with increased knowledge of how to organize and apply family financial records properly and correctly from an early age, PKK mothers at Villa Muka Kuning Batam Housing can prevent and limit unimportant financial expenditures, so that in the future there is no waste. During the visit, discussion with the head of RT 01 and regarding the appropriate schedule and time for the implementation of counseling. The service method used is to provide material about an introduction to simple financial management and governance for families, and discussions and questions and answers. The provision of this material is expected to be able to create awareness for PKK mothers in Villa Muka Kuning Housing Area RT 01 to be able to manage family finances properly and appropriately.